Empathy, values, personality, and mindfulness as psychosocial correlates of early STEM academic achievement: a cross-sectional exploration in Indian university students - Brahmi, Mannu; Soni, Dushyant; Jain, Harshita; Kumar, Jyoti (Frontiers in Education, 2025)
IntroductionTraditional models of academic achievement in STEM fields predominantly emphasize cognitive ability, overlooking the influence of psychosocial factors. Recent research in holistic and social-emotional learning has found that attributes such as empathy, mindfulness, personal values, and personality traits may contribute to learning and performance outcomes. This study examines the associative value of these psychosocial factors toward early STEM proficiency in Indian university students.MethodsA cross-sectional design was employed with two samples. Sample 1 (n = 580) completed self-report measures assessing trait empathy (IRI), personal values (PVQ-RR), personality (IPIP-BFM-50), and trait mindfulness (FFMQ-39), along with self-reported high school STEM academic scores in mathematics and science. A smaller subset, Sample 2 (n = 97), participated in a 50-min Ānāpānasati-derived breath-based meditation induction followed by the Amsterdam Resting-State Questionnaire (ARSQ) self-report administration to assess state mindfulness. Correlations were followed by hierarchical regression analyses, controlling for gender, university STEM status, and their interactions, to determine the incremental predictive value of the psychosocial variables.ResultsFindings revealed that cognitive empathy (especially, perspective-taking) and self-direction values were modest yet significantly associated with academic performance, particularly in science. Additionally, openness to experience emerged as a positive correlate, while state mindfulness—specifically the planning dimension—showed robust associations with higher academic scores. Hierarchical models confirmed that these variables contributed incremental variance beyond traditional demographic controls.DiscussionThe findings support a multidimensional understanding of early STEM proficiency, wherein psychosocial facets complement cognitive ability in shaping academic outcomes. These results have implications for educational interventions, emphasizing the integration of socio-emotional learning and mindfulness training in STEM curricula.